Case report: BCL-2 and CD31 immunoexpression related to clinical and histopathological evaluation of renal dysplasia in a Welsh Corgi Puppy - Le, Trung Quang; Pluemhathaikij, Latticha; Chankow, Katriya; Radtanakatikanon, Araya; Rungsipipat, Anudep; Rattanapinyopituk, Kasem (Frontiers in Veterinary Science, 2022)
A case of renal dysplasia (RD) in Welsh Corgi dog has been reported. Clinically, the affected three-month-old, female, Welsh Corgi dog showed unclear symptoms of chronic kidney disease. Grossly, both left and right kidneys revealed cystic hypoplasia. Histologically, the primary lesions included immature or fetal glomeruli/tubules, proliferative arterioles, persistent metanephric ducts, persistent mesenchyme, and atypical tubular epithelium were presented. A group of degenerative and inflammatory lesions consisted of interstitial nephritis, interstitial fibrosis, and mineralization of tubules were found. Immunohistochemically, the epithelial cells of immature (fetal) tubules had BCL-2 labeling whereas CD31 (PECAM-1) was labeled in the endothelial cells of the proliferative arterioles. The immunohistochemical findings were confirmed and consolidated with the routine histopathological findings. This study was the first demonstration of the clinical, histopathological, and immunohistochemical features of RD disease in a Welsh Corgi puppy.